Appraisal in translational novel A Thousand Splendid Suns from English to Indonesian language - Munir, Mohammad Rizaqi; Baskoro, Bernardinus Realino Suryo (Aksara: Jurnal Bahasa dan Sastra, 2022)
This research aimed to analyze appraisal system in the translation novel entitled A Thousand Splendid Suns. The method is descriptive comparative using appraisal theory by Martin and White. The results show that the three appraisal systems, namely attitude, engagement, and graduation, were found with different numbers which indicated differences in assessment between writers and translators. The analysis concluded that the equivalence of the appraisal system needs to be carried out to keep the author’s emotions, feelings, or attitudes in target text through evaluation language by the translator. It will also improve the quality of the translation.